INOVASI PENDIDIKAN AGAMA ISLAM - Muhammad Nur Hadi; Syaifullah; Wiwin Fachrudin Yusuf (Mu'allim, 2022)
This research is motivated by the current condition of Islamic religious education in Indonesia, which is still experiencing problems in various aspects and efforts to improve it have not been carried out in a basic way, seeming improvised. The government's attention to Islamic education is very small, on the other hand the government expects the people to have a socialist and religious spirit. It can be said that Islamic education in Indonesia occupies a "second class" in a Muslim-majority society. Social change is essentially a part of cultural change. Aspects of culture are art, science, knowledge, technology, philosophy. Ibn Khaldun said in his muqodimah there is no human society that does not change, meaning that the work of stopping the course of change is an impossible job. In social change, an in-depth philosophical study is needed to produce values ​​that can bring more benefits to society, to realize the values ​​contained in philosophy can be pursued in various ways, one of which is through education. With education, humans can communicate their culture and intellectual heritage to future generations, and provide inspiration and life goals.